The Nature of Disasters - Bricker, Jeremy; Pelupessy, Dicky (Journal of Delta Urbanism, 2025)
The dialogue between Jeremy Bricker and Dicky C. Pelupessy explores the fundamental nature of disasters, questioning the balance between natural forces and human influence while exploring themes of responsibility, risk perception, and preparedness. Drawing from Dicky’s essay Earth, Humankind, and the Haze Disaster, the discussion challenges the idea that the earth itself is vengeful, arguing instead that humans perceive natural events as acts of rage. It highlights humanity’s propensity to take risks and the misconception that disasters are purely natural occurrences. Instead, what we call a disaster is often the consequence of one—the result of human choices and vulnerabilities. For instance, as Dicky’s essay illustrates, in an earthquake, deaths are not caused by the quake itself but by collapsing structures—a failure to account for seismic risks that exceed a building’s capacity. Curated by guest editor Tara Kanj and chief editor Fransje Hooijmeijer, this transcribed dialogue brings together backgrounds in psychology, engineering, and design. Through cases from the Netherlands, Indonesia, and the United States, it highlights the complex interplay between environmental forces and human decisions that shape them.